2013
DOI: 10.1002/cbf.2940
|View full text |Cite
|
Sign up to set email alerts
|

SOCS and diabetes—ups and downs of a turbulent relationship

Abstract: Diabetes mellitus is one of the most emerging diseases threatening the present world. Thus, intensive investigations are carried out to better understand the mechanisms occurring in type 1 (T1D) and 2 (T2D) diabetes, and to elaborate more potent methods to fight the disease. In this aspect, the suppressors of cytokine signalling (SOCS) are one of the most studied factors of recent years. SOCS proteins have been discovered as cytokine pathway inhibitors; however, presently, their influence seems wider. Most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 106 publications
(388 reference statements)
0
19
0
Order By: Relevance
“…Several studies have reported intriguing properties of SOCS proteins in relation to the pathogenesis of diabetes mellitus. 21,22,24 In fact, SOCS1 knockout mice exhibit a low blood glucose level and increased insulin signaling, 21,35 thus suggesting SOCS as a link between elevated levels of cytokines and insulin resistance. However, SOCS1 induction protects β-cells in vitro, 36 with target expression of SOCS1 preventing diabetes mellitus in the nonobese diabetic mouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported intriguing properties of SOCS proteins in relation to the pathogenesis of diabetes mellitus. 21,22,24 In fact, SOCS1 knockout mice exhibit a low blood glucose level and increased insulin signaling, 21,35 thus suggesting SOCS as a link between elevated levels of cytokines and insulin resistance. However, SOCS1 induction protects β-cells in vitro, 36 with target expression of SOCS1 preventing diabetes mellitus in the nonobese diabetic mouse.…”
Section: Discussionmentioning
confidence: 99%
“…8,[17][18][19] JAK/STAT is also a critical inflammatory mechanism by which hyperglycemia contribute to the pathogenesis of diabetes mellitus and its complications. [20][21][22] In fact, classical STATresponsive inflammatory genes comprise a wide array of genes including cytokines, chemokines, enzymes, vasoactive proteins, and proto-oncogenes, 7,9,10 many of them also upregulated by diabetic conditions.…”
mentioning
confidence: 99%
“…Increased by cytokine signaling, SOCS-3 is considered to be a key link between inflammation and insulin resistance. It has been demonstrated that SOCS-3 is able to inhibit the insulin signal pathway; SOCS-3 overexpression in the liver leads to insulin resistance and hepatic steatosis [36]. Inhibition of SOCS-3 in the livers of db/db mice by antisense treatment improved insulin sensitivity and led to the dramatic amelioration of hepatic steatosis and hypertriglyceridemia [37].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The JAK/STAT pathway is negatively regulated via various mechanisms, including the suppressor of cytokine signaling (SOCS) proteins, which have been identified as negative feedback regulators of cytokine signaling, and have been reported to be involved in the regulation of inflammatory responses (1317). The mammalian cytokine-inducible SH2-containing protein (CIS)/SOCS family consists of 8 members, including CIS and SOCS1-7 (18).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SOCS-modulating properties have been attributed to pharmacological agents that are currently used for the treatment of diabetes (17). The present study aimed to investigate the function of SOCS3 in lung cells and to explore the implication of the JAK2/STAT3 signaling pathway in the molecular mechanisms underlying the effects of SOCS3 in hyperglycemia-induced lung injury.…”
Section: Introductionmentioning
confidence: 99%